2002
DOI: 10.2172/860130
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Hydroxide Extraction From Caustic Leaching Solutions

Abstract: SummaryThis report describes experiments conducted to demonstrate the proof-of-principle of a method to recover NaOH from Hanford tank sludge leaching solutions. Aqueous solutions generated from leaching actual Hanford tank waste solids were used. The process involves neutralization of a lipophilic weak acid (t-octylphenol was used in these experiments) by reaction with NaOH in the aqueous phase. This results in the transfer of Na into the organic phase. Contacting with water reverses this process, reprotonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…14 Applied development was spun-off into a separately funded one-year project that demonstrated that recovery of NaOH from actual waste is possible for recycle to sludge washing. 21 Although the concept appears viable, issues identified include selectivity, phase behavior, and stripping efficiency. The first observation of SPHE was communicated, 22 wherein it was shown that enhanced NaOH extraction may be effected by combining fluorinated alcohols with macrocyclic extractants.…”
Section: Summary Of Prior Resultsmentioning
confidence: 99%
“…14 Applied development was spun-off into a separately funded one-year project that demonstrated that recovery of NaOH from actual waste is possible for recycle to sludge washing. 21 Although the concept appears viable, issues identified include selectivity, phase behavior, and stripping efficiency. The first observation of SPHE was communicated, 22 wherein it was shown that enhanced NaOH extraction may be effected by combining fluorinated alcohols with macrocyclic extractants.…”
Section: Summary Of Prior Resultsmentioning
confidence: 99%
“…Although the donor-acceptor properties of 1-octanol are well-suited for PHE, its ability to solubilize appreciable amounts of water and its high viscosity are undesirable in an industrial application. At high sodium loading, expansion of the organic phase volume was observed with 1-octanol as the diluent , and in some cases, gelling of the loaded solvent occurred (Lumetta et al 2002). Aliphatic diluents are usually preferred for industrial solvent extraction processes.…”
Section: Research Progressmentioning
confidence: 99%
“…At high sodium loading, the volume of 1-octanol organic phase volume expanded, [6] and in some cases, the loaded solvent gelled. [7] Aliphatic hydrocarbon diluents are usually preferred for industrial solvent extraction processes. However, they entail trade-offs, such as poor solvation of the ionic species leading to very weak extraction, particularly of the alkali metal ions.…”
Section: Introductionmentioning
confidence: 99%